Public management and governance/ edited by Tony Bovaird and Elke Loffler - Bovaird, Tony (ed.) (London, 2003)
The book includes discussion questions, group and individual exercises, case studies and further reading, making it essential reading for all students on specialist undergraduate and postgraduate courses in Public Services Management, Public Administration, Government and Public Policy.
Keywords: Public administration